FITBALL GYMNASTICS AS A MEAN OF KEEPING AND IMPROVEMENT OF SCHOOLCHILDREN'S HEALTH ON PE LESSONS - Victor Lukyanenko; Natalia Mukhanova; Elena Coleco (Вестник Северо-Кавказского федерального университета)
New forms of PE studies get big popularity among schoolchildren. With the aim of increasing of schoolchildren's interest and motivation, elements of some new forms of studies with physical exercises can be included in contents of PE lessons. It can be football - gymnastics. This is one of new forms of studies relating to improving gymnastics. These days there are different health programmes on football-gymnastics, which elements can be used on the lessons of physical culture with the aim of keeping and improving of schoolchildren's health.